2012
DOI: 10.1186/1471-2164-13-665
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) cistrome reveals novel co-regulatory role of ATF4

Abstract: BackgroundThe present study coupled expression profiling with chromatin immunoprecipitation sequencing (ChIP-seq) to examine peroxisome proliferator-activated receptor-β/δ (PPARβ/δ)-dependent regulation of gene expression in mouse keratinocytes, a cell type that expresses PPARβ/δ in high concentration.ResultsMicroarray analysis elucidated eight different types of regulation that modulated PPARβ/δ-dependent gene expression of 612 genes ranging from repression or activation without an exogenous ligand, repressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 57 publications
7
78
0
Order By: Relevance
“…Microarray Analysis-Total RNA was isolated as previously described (37). Purified RNA was assessed by GeneChip Mouse Gene 2.0 ST array (Affymetrix, Santa Clara, CA) following the manufacturer's recommended procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray Analysis-Total RNA was isolated as previously described (37). Purified RNA was assessed by GeneChip Mouse Gene 2.0 ST array (Affymetrix, Santa Clara, CA) following the manufacturer's recommended procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Purified RNA was assessed by GeneChip Mouse Gene 2.0 ST array (Affymetrix, Santa Clara, CA) following the manufacturer's recommended procedures. The robust multichip average approach was applied to normalize microarray data as previously described (37). The p value Ͻ 0.05 and a fold change of 1.5 in the intensity of signals were used to identify genes that were significantly regulated by ethanol treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptors (PPARs 3 : PPARA, PPARD (also referred to as PPAR␤, PPAR␦, PPAR␤/␦, or NUC1), and PPARG) are ligand-activated transcription factors that control a variety of biological processes in dynamic fashion (4). Previous studies showed that all three PPARs are expressed in both somatic and spermatogenic cells in the testis (5-7).…”
Section: Tight Junctions In Sertoli Cells Thus Confirming a Requiremmentioning
confidence: 99%
“…Gene expression analysis studies in combination with chromatin immunoprecipitation sequencing (ChIP-seq) have identified direct and indirect PPAR-δ regulated genes (21, 22). Well-documented direct targets of PPAR-δ include genes involved in fatty-acid oxidation and lipid metabolism such as Cpt1a , Fabp1 and Pdk4, whereas pro-inflammatory cytokines like TNF-α and IL-6 are regulated indirectly.…”
Section: Introductionmentioning
confidence: 99%